2007
DOI: 10.1007/s11845-007-0003-4
|View full text |Cite
|
Sign up to set email alerts
|

Are routine peritoneal fluid cultures during appendicectomy justified?

Abstract: Intra-operative peritoneal cultures during appendicectomy do not significantly contribute towards patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
1
4
0
1
Order By: Relevance
“…However, the patient was treated with Tazocin, an antibiotic that was not listed on the sensitivities obtained from the pus samples. The results of this study suggests that obtaining routine pus samples in complicated appendicitis for cultures and sensitivity can be abandoned which is similar to findings in previous literature (4,5,(11)(12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 89%
“…However, the patient was treated with Tazocin, an antibiotic that was not listed on the sensitivities obtained from the pus samples. The results of this study suggests that obtaining routine pus samples in complicated appendicitis for cultures and sensitivity can be abandoned which is similar to findings in previous literature (4,5,(11)(12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 89%
“…The value of routine culture data in guiding antimicrobial therapy for lower-risk patients with CA-IAI has not been rigorously evaluated in prospective trials [186]. Nevertheless, a number of observational studies have suggested that these cultures rarely, if ever, provide information useful to the clinician [187][188][189][190][191]. The majority of lower-risk patients with CA-IAI are successfully treated with standard approaches to source control and antimicrobial therapy.…”
Section: Antimicrobial Therapymentioning
confidence: 99%
“…Of note, current guidelines are based largely on data from perforated appendicitis; other patients with CIAI have not been evaluated. The present results suggest that taking intra‐abdominal cultures reduces mortality from CIAI.…”
Section: Discussionmentioning
confidence: 99%
“…Recent guidelines recommend obtaining cultures from peritoneal fluid in high‐risk patients and those with healthcare‐associated infection. However, there is little evidence to support these recommendations, most of which are based on studies of patients with perforated appendicitis. These observational studies have suggested that intra‐abdominal cultures rarely provide information that is useful to the clinician.…”
Section: Introductionmentioning
confidence: 99%